Exploring University Staff Views on Providing Continuing Education for Professional Engineers in Denmark: Using the Q Methodology - Bente Nørgaard; Juebei Chen; Ida Korning; Xiangyun Du (Education Sciences)
This article reports on a study examining 28 university engineering educators’ viewpoints on how to provide continuing education for professional engineers in a Danish university context. The Q methodology was adopted to collect and analyze data qualitatively and quantitatively. Three significantly different viewpoints were identified, prioritizing (1) a continuing engineering education (CEE) business model as an institutional priority, (2) organizational structure, and (3) pedagogy inspired by problem-based learning (PBL). The study also captured consensus on the importance of identifying the industry’s need for CEE organizations. The results reveal that CEE development needs to address diverse voices from different stakeholders, including leadership, academic faculty, and administrators; thus, suggestions from an organizational change perspective are proposed in four key aspects of CE organizations.